Redistributive effects of China's urban–rural resident basic medical insurance: a theoretical model and empirical analysis - Ji, Wenfang; Chu, Fuling; Qin, Yi (Frontiers in Public Health, 2025)
IntroductionAs a core pillar of China's social-security system, the Urban–Rural Resident Basic Medical Insurance (URRBMI) redistributes income and promotes equitable access to health care, offering globally relevant lessons for similar economies. Despite its rapid expansion, the redistributive performance of URRBMI has not been rigorously assessed. Clarifying the conditions under which it narrows or widens income gaps—and the extent to which it does so—is therefore essential for evidence-based policy reform.MethodsWe develop an institutional-level theoretical model that treats the Gini coefficient of disposable income as the primary redistributive indicator. Using household-level data, we compute Gini coefficients before and after insurance reimbursement; a post-reimbursement decline denotes positive redistribution, whereas an increase signals negative redistribution. The analysis disaggregates medical expenditure into low, medium, and high tiers and compares outcomes across insured and uninsured groups. Region-specific estimates are produced for Northeast, Central, and other macro-regions to capture spatial heterogeneity.ResultsEmpirical estimates for the national sample confirm that URRBMI reduces income inequality overall. Redistribution is strongest in the Northeast and weakest in Central China. Expenditure-level analysis shows that when inpatient expenses lie below the deductible, the scheme exerts no redistributive force; once the deductible is crossed, reimbursements narrow income disparities, and the magnitude of redistribution rises with the reimbursement rate. Relative to the uninsured, non-participation is advantageous only when inpatient spending remains below the deductible; beyond the deductible, participation and reimbursement yields superior and progressively stronger redistributive outcomes as expenditure tiers increase.DiscussionURRBMI still faces three key challenges: the contribution mechanism is not income-related, benefit packages vary markedly, and the fund relies heavily on fiscal transfers while exhibiting limited risk-pooling capacity. To enhance redistributive effectiveness, we recommend mandatory enrolment with income-proportional contributions, higher benefit levels, and raising the pooling level of the basic medical insurance fund, while merging the urban employee basic medical insurance scheme with the urban and rural residents' basic medical insurance scheme.